KEBIJAKAN AMERIKA SERIKAT DALAM MENJAGA EKSISTENSI PASAR GLOBAL MELALUI PERUSAHAAN COCA-COLA (KAPITALISME : COCA COLONIZATION) - Nurmamurti, Resitaka Aulia; Navila, Shendy Friska; Budi, Ema Sulistyaning; Amanda, Anggie Chyntia; Kholifah, Diah Siti; Rizky, Lucitania (Universitas Panca Marga, 2022)
Abstract The international economy certainly cannot be separated from the United States economy. The United States of America is the country with the largest economy in the world. Within the framework of Neoliberalism, the economy cannot be separated from state intervention. The state can carry out various policies with the aim of achieving the national interest and profit as much as possible. This paper is intended to obtain the United States' efforts to build Coca Colonization from the point of view of the economic paradigm of capitalism and neoliberalism. Coca-Cola itself is a drink that comes from America where it has been around since 1886 and is the number one coke in the world. The existence of Coca-Cola itself already existed during the World War period, where Coca-Cola came along with the presence of United States troops and there were 60 Coca-Cola bottling factories around the world which were started when there was an American military operation. Coca-Cola is considered an American culture and an unofficial ambassador for the American lifestyle itself. Using literature studies through various news, documentation, scientific journals, this research resulted in the United States' efforts including building nation branding. This nation branding is very strong so that local products are difficult to escape from the influence of product colonization instilled by the United States globally. Keywords: United States of America, Coca Colonization, Nation branding, Coca-Cola